Rectal Flap Experience in High Transsphincteric Cryptoglandular Anal Fistula - Kılıç, Ali; Tilev, Sırma Mine; Başak, Fatih; Şişik, Abdullah (Journal of Surgery and Medicine, 2019)
Aim: Despite many treatment modalities, anal fistula disease remains an important problem. High recurrence rates have been reported in the surgical treatment of complicated anal fistulas. We hereby present complicated anal fistula patients treated with rectal advancement flaps. Methods: Patients who underwent rectal advancement flap surgery by a single surgeon between 2009 and 2019 were analyzed in this retrospective cohort study. Demographic data, number of previous operations, recurrence rate and complications were recorded. Results: Twenty patients (15 males and 5 females) underwent surgery with the rectal advancement flap technique. Nine patients had more than one previous operation. Seton, partial fistulectomy and curettage were the most performed operative techniques in their previous surgeries. The mean follow-up period was 31 months (3-74). Among 13 patients with follow up periods longer than 12 months, 3 patients had recurrences (23%), all of which had been previously operated twice or more. Conclusion: Although rectal advancement flap is not the first choice in the treatment of complicated and high transsphincteric fistulas, it still maintains its importance. Experienced surgeons prefer this method due to its sphincter-sparing nature. In our study we detected a recurrence rate of 23% and incontinence rate of 5%, which was thought to be related to previous surgeries.